PERBANDINGAN REGRESI ROBUST DENGAN OLS PADA PRODUKSI UBI JALAR PROVINSI JAWA TENGAH TAHUN 2015 - Endah Suryaningsih Utami; Abdul Karim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Ordinary Least Square (OLS) or Method of Least Squares (MKT) is one of the methods used to get the estimator parameter values of the regressionmodel, but the resultant estimator is strongly influenced by the outlier data.Although the parameter estimator results are strongly influenced by the data,it can use Robust Regression method to handle it so it is not necessary tothrow out the data, as it may be enough to provide information. The application of the two methods is on the production of sweet potato data per regency and city in Central Java province in 2015. The results showed that the data is not normally distributed, both OLS and robust model. Keywords: OLS, Robust Regression, Sweet Potato Production